Simplifying HPC Application Development with OpenMP Cluster and Unified Memory - Cléto, Jhonatan; Yviquel, Hervé; Pereira, Marcio M.; Araújo, Guido (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP); 2023: Anais da XIV Escola Regional de Alto Desempenho de São PauloDO - 10.5753/eradsp.2023.231898, 2023)
As accelerators such as GPU and FPGA become more common in HPC systems, programming for these systems becomes more challenging due to, for example, the additional layer of memory management. This paper presents an extension to the OpenMP Cluster that integrates CUDA’s Unified Memory management. Evaluation using a synthetic benchmark reveals that while this extension simplifies the development of GPU-based OMPC applications, further optimization is required to reduce its impact on performance.